An Analysis of Physician Productivity and Self-Sustaining Revenue Generation in a Free-Standing Emergency Department Medical Scribe Model. (29th December 2015) - Dawkins, Brody; Bhagudas, Komal N.; Hurwitz, Joshua; Tyndall, J. Adrian; Guerra, Marcelo E.; Falgiani, Michael; Payton, Thomas F.; Allen, Brandon R.
Abstract : Objectives . A free-standing emergency department (FSED) is a facility that provides comprehensive emergency medical care similar to a traditional emergency department but is not attached to a hospital campus. Medical scribes are increasingly likely to work in free-standing emergency departments. The purpose of this study was to retrospectively investigate the benefits of a scribe program in an FSED. Methods . A retrospective, Institutional Review Board-approved analysis from December 1, 2013, to February 1, 2015, of free-standing emergency department medical data was extracted to determine if scribed charts resulted in increased revenue and improved throughput. Results . When scribes are present in the FSED there is a small, but statistically significant, decrease in time from patient arrival to provider by 2.74 minutes. Scribed charts collected $4.69 more per chart and resulted in an increase in productivity. Incremental cost effectiveness ratios resulted in proven cost-utility with a net-positive effect. Conclusion . While there are some gains in terms of operational metrics and provider productivity with the addition of scribes to a free-standing emergency department, there is a net-positive financial impact of scribes. Implementing a scribe program at a FSED is cost-effective and justified from both an operational and a financial analysis.